Two-Year Mortality and Prognostic Factors in Sepsis: A Prospective Cohort Study of 714 Danish Emergency Department Patients - Nielsen, Finn; Chafranska, Lana; Sørensen, Rune; Schmidt, Thomas; Abdullah, Osama (Clinical epidemiology, 2025)
Given the lack of data on long-term outcomes among patients with sepsis, this study aimed to examine all-cause 2-year mortality and factors associated with mortality in adults admitted to an emergency department with sepsis. Prospective cohort study. This study included all emergency department patients admitted with sepsis to Slagelse Hospital, Denmark, between October 1, 2017, and March 31, 2018. Data on patients with infectious diseases was prospectively extracted from electronic health records during the study period. Sepsis was defined as a Sequential Organ Failure Assessment (SOFA) score ≥ 2 from baseline. The outcome was 2-year all-cause mortality. The Kaplan-Meier method was used to estimate the mortality. Cox regression analyses were used to compute adjusted hazard ratios (aHR) with 95% confidence intervals for prognostic factors associated with mortality. A total of 714 patients (58.4% men) with a median age of 75 years were diagnosed with sepsis. After two years, 354 (49.6%; 45.9-53.3) patients had died. Factors associated with elevated mortality risk included age (< 65 years as reference) 65-85 years (aHR 1.89; 1.35-2.64) or age > 85 years (aHR 2.99; 2.07-4.31); SOFA score > 4 (aHR 2.45; 1.82-3.30) (score of 2 as reference); and history of malignancy (aHR 1.91; 1.44-2.53), ischemic heart disease (aHR 1.38; 1.03-1.84), dementia (aHR 1.84; 1.34-2.53), previous sepsis admission (aHR 1.45; 1.15-1.82), new-onset atrial fibrillation (aHR 1.56; 1.05-2.34), and mildly decreased (6.9-7.9 mmmol/L) hemoglobin values (aHR 1.68; 1.29-2.19) and significantly decreased (<6.9 mmol/L) hemoglobin values (aHR 2.30; 1.74-3.02) with normal range (≥ 8mmol/L) as reference. Skin infection was associated with diminished mortality risk (aHR 0.50; 0.29-0.85) compared to patients with other sources of infection. Sepsis is associated with a poor prognosis. Our findings underscore the prognostic effects of age, SOFA score, and specific comorbidities on 2-year mortality among patients with sepsis.